IMPLEMENTATION OF NTB LOCAL GOVERNMENT POLICY FOR SOCIAL SERVICES FOR PEOPLE WITH DISABILITIES IN ACHIEVING INDEPENDENCE - Ratin Wahyu Juni Atma; Lingga Apri Murtini; Norsuhaily Abu Bakar; Indah Nurhakiki (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
The focus of this research is the lack of provision of accessibility and public facilities specifically designed for persons with disabilities that aim to facilitate their activities outside the home. This gap can occur due to the lack of implementation of the NTB Regional Government Regulation No. 4 of 2019 concerning the protection and fulfillment of the rights of persons with disabilities. This study is also to find out the efforts of the village-level government in providing services to persons with disabilities in the form of assistance for accessibility of public services and individual services. This study uses a qualitative approach with the type of phenomenology. In obtaining data, this researcher used observation, interview, and documentation techniques. This research was conducted in Mujur Village, East Praya District, Central Lombok Regency. Based on the results of the research that has been done, it can be concluded that the implementation of policies from the NTB Regional Government Regulations that have been established by the NTB Provincial Government has not been implemented properly and evenly. Therefore, it is recommended that the local government, especially the Central Lombok Regency Government and the Mujur Village government, make efforts to provide adequate facilities for persons with disabilities.